2020
DOI: 10.1080/02786826.2019.1708260
|View full text |Cite
|
Sign up to set email alerts
|

Precision characterization of three ultrafine condensation particle counters using singly charged salt clusters in the 1–4 nm size range generated by a bipolar electrospray source

Abstract: Molecular singly charged clusters generated by electrospray sources are commonly used for calibration measurements of ultrafine Condensation Particle Counters (CPCs) in the sub-2 nm size range. This technique has been limited to the smallest singly charged clusters. In this study, we used a bipolar electrospray source combining two electrosprays of opposite polarities to generate singly charged clusters of ammonium salts dissolved in acetonitrile, i.e., tetra-heptyl ammonium bromide (THABr) and tetra-butyl amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Our results for Ag and NaCl are in perfect agreement with the results for a dry aerosol flow ofTauber et al (2019a). AsBrilke et al (2020) highlight, there is no composition dependence of the detection efficiencies of the TSI 3776*. The 50 % cut-off diam-5 eters for negatively-charged Ag seeds presented by the authors are also confirmed by our measurements.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Our results for Ag and NaCl are in perfect agreement with the results for a dry aerosol flow ofTauber et al (2019a). AsBrilke et al (2020) highlight, there is no composition dependence of the detection efficiencies of the TSI 3776*. The 50 % cut-off diam-5 eters for negatively-charged Ag seeds presented by the authors are also confirmed by our measurements.…”
supporting
confidence: 90%
“…the TSI 3772, 15 the TSI 3776 and the Airmodus A20, show the expected activation pattern: BCYO x and Ag seeds are activated at smaller diameters compared to (NH 4 ) 2 SO 4 and NaCl seeds. The Airmodus A20 reaches its plateau, located at detection efficiency values of about 0.9 at 20 nm.Astoundingly, the TSI 3776* shows barely no composition dependence of the 50 % cut-off diameters, thereby confirming the results for ofBrilke et al (2020) for Ag seeds. There is no significant difference between the smallest and the largest 50 % 20 cut-off diameter, which are centered around 2.1 nm.…”
supporting
confidence: 79%
See 3 more Smart Citations